Features Of the Course and Treatment of Aggressive Forms of Paradontitis - Razzokova Shohista Bakhtiyorovna; Anvarova Mukhtasar Anvarovna (Zien Journals, 2021)
To date, there is no controversies in periodontology on etiological, pathomorphological, diagnostic immunological and histological aspects associated with periodontitis. Nevertheless, the issues in differential diagnostics of various forms periodontitis, which have a number of clinical differences, remain topical. Aggressive periodontitis is rare, and therefore it is not well understood. In this regard, practitioners often believe that differential diagnosis between chronic and aggressive periodontitis is not necessary, difficult, and sometimes even impossible. This formulation of the question leads to incorrect clinical thinking. The purpose of the publication is to highlight this issue, and the data presented in the article demonstrate the differences between chronic and aggressive periodontitis, which allows more rapid identification of initial forms of periodontitis and precise differential diagnosis, which in the future will affect both planning, results of treatment and their stability as well.
Keywords: aggressive periodontitis; chronic periodontitis; differential diagnosis